Short- and long-term effectiveness of a three-month individualized need-supportive physical activity counseling intervention at the workplace. (December 2017) - Arrogi, Anass; Schotte, Astrid; Bogaerts, An; Boen, Filip; Seghers, Jan
Abstract Background The objective of the present study was to evaluate the short- and long-term intervention and mediation effects of a 3-month individualized need-supportive physical activity (PA) counseling intervention on employees' PA and sedentary behavior. Methods Insufficiently active employees (n  = 300; mean age 42 ± 9 years; 78% female) were recruited from a large pharmaceutical company in Flanders, Belgium. A quasi-experimental design was used in which the intervention group (N  = 246) was recruited separately from the reference group (N  = 54). Intervention group participants received a 3-month behavioral support intervention, which consisted of two one-hour face-to-face counseling sessions and three follow-up counseling contacts by e-mail or telephone at weeks three, six and nine. PA counseling, delivered by qualified PA counselors, aimed to satisfy participants' basic psychological needs for autonomy, competence, and relatedness. Reference group participants did not receive individualized PA counseling. Outcome measures included objectively assessed and self-reported PA and sedentary time and psychological need satisfaction. Assessments were held at baseline, immediately after the intervention (short-term) and 6 months post-intervention (long-term). Mixed model analyses and bootstrapping analyses were used to determine intervention and mediation effects, respectively. Results The intervention group increased weekday daily steps both in the short- and long-term, while the reference group showed reductions in daily step count (ES = .65 and ES = .48 in the short- and long-term, respectively). In the short-term, weekday moderate-to-vigorous PA increased more pronouncedly in the intervention group compared to the reference group (ES = .34). Moreover, the intervention group demonstrated reductions in self-reported sitting time during weekends both in the short- and long-term, whereas the reference group reported increased sitting time (ES = .44 and ES = .32 in the short- and long-term, respectively). Changes in perceived autonomy and competence need satisfaction mediated the long-term intervention effects on daily step count. Conclusions A 3-month individualized need-supportive PA counseling intervention among employees resulted in significant and sustained improvements in weekday daily step count and in decreased self-reported sitting during weekends. Our findings contribute to the growing evidence of the long-term effectiveness of need-supportive PA counseling. Trial registration ClinicalTrials.govNCT01759927 . Registered December 30, 2012.